Análise de publicações referente a intervenções para a dor crônica: uma revisão de escopo - Manin, Gabriela Zenaro (Universidade Federal de São Carlos, 2024)
Chronic pain is a globally recognized and multifaceted condition, notable for its complexity, causes, and health impacts. Primary Health Care is of paramount importance for the implementation of Multidisciplinary Care Lines to ensure comprehensive treatment. This study aims to support innovative practices within the Unified Health System, acknowledging the need for more efficient approaches to address the growing prevalence of chronic pain. Objectives: The objectives include mapping the feasibility of a multidisciplinary care line for chronic pain, analyzing literature on chronic pain, treatment, and professional practices; proposing guidelines and creating a care line. Methodology: The study's methodology involves a scope review and documentary analysis with a qualitative approach, following the recommendations of the Joanna Briggs Institute and PRISMA-ScR. It encompasses literature on chronic pain, healthcare, and legislations, aiming to map and identify gaps. The research strategy involved terms such as "Chronic Pain," "Delivery of Healthcare," and "Healthcare Models." The search took place on databases such as SciELO, PubMed, MEDLINE, and Cochrane, with defined inclusion and exclusion criteria. After study selection, data extraction followed a validated instrument, and the analysis considered the level of evidence and grades of recommendation. Results were organized into categories such as articles, protocols, and recommendations, providing a comprehensive view of the topic in Primary Health Care. Results and Discussion: The scope review highlighted the effectiveness of multidisciplinary approaches, such as psychological interventions and physical treatments, emphasizing the importance of Cognitive-Behavioral Therapy (CBT). It revealed the complexity of chronic pain management, underscoring the need for an integrated approach. It noted the diversity of factors influencing pain perception, including psychosocial aspects and physiological mechanisms. The study addressed challenges faced by healthcare professionals and the urgency of evidence-based practices. It emphasized the importance of self-management of chronic pain with effective interventions and governmental recognition.
Analysis of publications regarding interventions for chronic pain: a scoping review
Keywords: Atenção Primária à Saúde; Dor crônica; Modelos de assistência à saúde; Atenção à saúde; Prestação integrada de cuidados de saúde; Assistência integral à saúde; Primary health care; Chronic pain; Health models; Delivery os health care; Delivery os health care integrated; Comprehensive health care; CIENCIAS DA SAUDE